Assessment and Evaluation of Blended Cement Using Bamboo Leaf Ash BLASH Against Corrosion - Cecielle N. Dacuan; Virgilio Y. Abellana; Hana Astrid R. Canseco (Civil Engineering Journal, 2021)
Concrete provides a high degree of protection against corrosion of embedded steel reinforcement. Owing to the harsh environmental conditions and the presence of aggressive elements from the marine environment, deteriorating corrosion affects the durability of reinforced concrete structures. This study evaluated the effectiveness of bamboo leaf ash BLASH as a supplementary cementing material or admixture with Portland cement to improve the durability of reinforced concrete structures. Specimens of 0, 10, 15, and 20% BLASH mixtures were prepared using 16, 20, and 25 mm  steel reinforcements. A total of 100 cylindrical specimens were cast and used in this study. The specimens were accelerated by corrosion using impressed current techniques and a galvanostatic method in a simulated environment. The results show that specimens with a BLASH content of 10% exhibited superior performance and exhibited longer corrosion initiation and propagation times. It has a higher resistance to acid penetration and lower corrosion rates. The crack parameters of the specimen with BLASH admixtures, such as the crack width and crack frequency, were negligible. The use of BLASH as an admixture strengthens its durability and improves its residual strength and serviceability. Doi: 10.28991/cej-2021-03091707 Full Text: PDF